The Zero Divisor Graph of the Ring Zqp. - Shuker, Nazar H.; Rashed, Payman A. (Science Journal of University of Zakho, 2015)
In this paper we construct a star zero divisor graph from the zero divisor graph of the ring Zqp. The star zero divisor graph is obtained by removing some vertices from the zero divisor graph Γ(Zqp), in different ways , but the best way to get star zero divisor graph SΓ(Zqp) is by removing an odd number of zero divisors. Finally the crossing number, the girth and the diameter of this graph is also determined.